KIF11 inhibitors filanesib and ispinesib inhibit meningioma growth in vitro and in vivo - Jungwirth, Gerhard; Yu, Tao; Cao, Junguo; Alaa Eddine, Montadar; Moustafa, Mahmoud; Warta, Rolf; Debus, Jürgen; Unterberg, Andreas; Abdollahi, Amir; Herold-Mende, Christel (Cancer letters, 2021)
Treatment of aggressive meningiomas remains challenging due to a high rate of recurrence in higher-grade meningiomas, frequent subtotal resections, and the lack of effective systemic treatments. Substantial overexpression associated with a poor prognosis has been demonstrated for kinesin family member 11 (KIF11) in high-grade meningiomas. Due to anti-tumor activity for KIF11 inhibitors (KIF11i) filanesib and ispinesib in other cancer types, we sought to investigate their mode of action and efficacy for the treatment of aggressive meningiomas. Dose curve analysis of both KIF11i revealed IC50 values of less than 1 nM in anaplastic and benign meningioma cell lines. Both compounds induced G2/M arrest and subsequent subG1 increase in all cell lines. Profound induction of apoptosis was detected in the anaplastic cell lines determined by annexin V staining. KIF11i significantly inhibited meningioma growth in xenotransplanted mice by up to 83%. Furthermore, both drugs induced minor hematological side effects, which were less pronounced for filanesib. We identified substantial in vitro and in vivo anti-tumor effects of the KIF11 inhibitors filanesib and ispinesib, with filanesib demonstrating better tolerability, suggesting future use of filanesib for the treatment of aggressive meningioma.
Gesehen am 19.05.2021